In‐Air Bubble Phobicity and Bubble Philicity Depending on the Interfacial Air Cushion: Toward Bubbles Manipulation Using Superhydrophilic Substrates. (28th March 2019) - Xu, Bojie; Wang, Qianbin; Meng, Qing'an; He, Meijin; Guo, Cheng; Jiang, Lei; Liu, Huan
Abstract: Bubbles, a typical air‐in‐liquid system including both underwater and in‐air bubbles, are important phenomena involved in our daily life and engineering fields. So far, the fundamental and dynamics for in‐air bubbles largely remain unclear. Here, two typical in‐air wetting states of the bubble are revealed: the bubble‐phobic state in which a bubble with a perfect spherical shape stays on the liquid surface but without coalescence with the liquid; and the bubble‐philic state in which a bubble on the liquid substrate gives a quasi‐hemispherical shape. It is proposed that the bubble phobicity is a typical high‐energy state where the air cushion at the bubble/liquid interface plays a crucial role in preventing their coalescence by generating an energy barrier. By applying an external force to overcome the energy barrier, the bubble will distort and finally be stabilized in a bubble‐philic state. It is demonstrated that superhydrophilic substrates enable manipulating bubbles in air: a superhydrophilic surface with microscale hairy textures shows robust in‐air repellence to the bubbles, while a hemispherical bubble is capable of transport directionally in air on a superhydrophilic conical fiber. Here, the concept of superwetting into air‐in‐air system (liquid films) is promoted, which may open a new perspective in surface and interface chemistry. Abstract : Depending on the stability of interfacial air cushions, two typical wetting states of bubbles in air are suggested, the bubble‐phobic and the bubble‐philic state. By utilizing these two wetting states, both super‐repellence to bubbles and directional transfer of bubbles are enabled on superhydrophilic substrates, which represent a new mode of bubbles manipulation in air.